2021
DOI: 10.1049/hve2.12169
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism on improved surface flashover performances in vacuum of epoxy resin using fluorocarbon plasma treatment

Abstract: To improve the insulation, strength of materials is a permanent topic in the fields of high voltage and insulation, and surface insulation is one of the difficulties. Research shows that the surface fluorination by a non‐equilibrium plasma is a promising method to enhance the surface flashover characteristics of insulating materials. However, the determinants of flashover characteristics are so many that the mechanism is not well known. This paper aims to find out the reasons for the surface insulation improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…The inhibition effect of TFO is probably related to the strong electronegativity of Fluorine atoms. When the paper is subjected to a DC electric field, electrons passing through the interface of the TFO and the aramid will be easily captured by CF 3 and CF 2 , resulting the formation of negative groups to scatter the subsequent electron beam, which may hinder the carrier transport and discharge process [29].…”
Section: Conductivity and Dielectric Propertiesmentioning
confidence: 99%
“…The inhibition effect of TFO is probably related to the strong electronegativity of Fluorine atoms. When the paper is subjected to a DC electric field, electrons passing through the interface of the TFO and the aramid will be easily captured by CF 3 and CF 2 , resulting the formation of negative groups to scatter the subsequent electron beam, which may hinder the carrier transport and discharge process [29].…”
Section: Conductivity and Dielectric Propertiesmentioning
confidence: 99%
“…Comparatively, multipactor suppression is the more direct, effective, and frequently used strategy, which is based on the design principle to reduce the secondary electron yield (SEY) of the insulators and reduce the number of electrons available for SEEA. The SEY reduction approaches, including bulk insulation modification (e.g., chemical grafting [24,25], doping of functional fillers [26,27]) and surface treatment (e.g., fluorination [28,29], composite coating [30][31][32][33], plasma treatment [34][35][36], and thin film deposition [37,38]) have shown the ability of multipactor suppression to some extent. Nevertheless, most of these methods are collectively cumbersome and have poor mechanical stability.…”
Section: Introductionmentioning
confidence: 99%
“…As an emerging technology, plasma has received a lot of attention in the treatment of materials. Chen et al used He/CF 4 jet plasma fluorinated epoxy resin surface, and found through testing that the increase of roughness and grafting of fluorinated functional groups reduced the secondary electron emissivity and improved the material flashover performance [5] . Wang et al researched the effect of the deposition of silicon oxide (SiO x ) nanofilm on the surface of epoxy resin on its surface insulation properties.…”
Section: Introductionmentioning
confidence: 99%